Predicting the Drag Coefficient Characteristics of Ocean Bottom Unit (OBU) Float Array Model for Early Warning Tsunami Systems Using Computational Fluid Dynamics (CFD) Method - Kusuma, Yudiawan Fajar; Hariz, Ilham; Defianti, Hanni; Hakim, Buddin Al; Putra, Arfis Maydino F. (Mekanika: Majalah Ilmiah Mekanika, 2023)
The early tsunami warning system encompasses several complex components, one of which is the Ocean Bottom Unit (OBU) floater. This paper discusses the performance of various types of floater arrays for tsunami early warning systems using Computational Fluid Dynamics (CFD) simulations. The study focuses on coefficients, especially the drag coefficient, and the influence of the number of float arrangements on the flow pattern around the buoy or Ocean Bottom Unit (OBU) array. Among the five numerical simulation models, the six-couple floater has the highest drag and lowest lift coefficients, while the single floater has the lowest drag coefficient. The percentage of difference in drag coefficient between single floater and couple series floater is quite significant, reaching up to 50%. The moment coefficient is also affected by the number of floaters, with a series of five couple floaters having the highest moment coefficient at a Reynolds number (Re) of 2 × 106. The results indicate that the flow pattern becomes more complex as the number of floater arrays increases, which leads to more vortices between the floater, resulting in increased turbulence and drag coefficient.